(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Space transformation of dwelling house of reog community in Pendukuhan Gunungsari of Bejiharjo Village of Gunungkidul District The community of Pedukuhan Gunungsari, Bejiharjo Village, Karangmojo Subdistrict, Gunungkidul District has an art community called “Paguyuban Reog Keprajuritan” which is different from the Reog Ponorogo. This creative art community unites the whole society to gain prosperous, independent and peaceful life. The Reog community is able to shape a good, harmonious and caring social life and empower the economic sector of the community. The community creates a new communal space. This phenomenon causes spatial transformation or land conversion in Padungsuhan Gunungsari. The purpose of this study was to find out the change of space functions that occurred at the residence of the activists of the Reog community in Bejiharjo Village. This study is descriptive with a qualitative approach. Data collections were conducted by Direct observation, in-depth surveys, documentation, interviews and library research. Housing condition and activities of the community were the points of analysis. This study shows that the Reog community has strong potential but they do not yet have facilities that support their activities. © 2019 Welly Hartono